Rapid weight loss is not associated with competitive success in elite youth Olympic-style boxers in europe - Zubac, D.; Karnincic, H.; Sekulic, D. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To examine the influence of rapid weight loss (RWL) on competitive success in elite youth Olympic-style boxers. In addition, this study examined the practice and prevalence of weight reduction, weight-management protocols, and related symptoms in youth boxers from 12 European countries (N=83, all males, mean [SD] age 17.1 [0.9] y). Methods: The data were collected using an extensive questionnaire on weight cutting and its associated protocols and symptoms prior to highest-level continental championships. Competition results were obtained at follow-up using a dichotomous variable: medal winning vs nonwinning at the European Championships. Results: Binary logistic regression analysis indicated that "boxing experience" was significantly related to the criterion competitive outcome (odds ratio=1.33; 95% confidence interval, 1.06-1.66; Nagelkerke R2=.11), with a higher likelihood of competitive success for more-experienced boxers. Of all the youth boxers, only 25% were included in the RWL group, irrespective of their weight-class stratification. More than 45% of all the youth boxers self-reported the simultaneous combination of different weight-cutting methods that are known to be serious health hazards. Finally, 33% of the boxers experienced muscle weakness as a consequence of RWL. Conclusions: Our study provided evidence of pathogenic weight-management protocols that are widely adopted by youth boxers, and yet the present outcomes showed that RWL did not translate into competitive success in these elite Olympic-style boxers in Europe. Therefore, the authors suggest a mandatory educational program that should simultaneously target all the mentioned issues including both health- and performance-threatening consequences.